POLA PEMBERDAYAAN PT. KUSUMA SATRIA DINASASRI WISATAJAYA (KUSUMA AGROWISATA) TERHADAP PETANI - Novita Scorpioana Tokan; Rikawanto Eko Mulyawan; Umi Rofiatin (Universitas Tribhuwana Tunggadewi, 2021)
The most prominent sector in Indonesia and the livelihood of the Indonesian population is the agricultural sector. PT. Kusuma Agrowisata is a company engaged in apple agrotourism, but farmers which joined at PT. Kusuma Agrowisata does not use their potential to the fullest due to the education and knowledge of farmers and because it is still traditional there. So it is necessary to provide counseling to farmers about the government so that these creative and independent farmers are part of agricultural empowerment. This research aims to identify and analyze the pattern of community empowerment of PT. Kusuma Agrowisata. The method of collecting data was through interviews with 20 farmers. The data was analyzed by SWOT analysis. The results of this study state the pattern of farmer community empowerment at PT. Kusuma Agrowisata has two indicators, namely counseling and training.